Domain-Driven Design applied to land administration system development: Lessons from the Netherlands. (May 2021) - Oukes, Peter; Andel, Marc van; Folmer, Erwin; Bennett, Rohan; Lemmen, Christiaan
Abstract: The introduction or renewal of information systems conventionally begins with data modelling. In the domain of land administration, like others, the process is challenging: complex laws and regulations, lengthy process descriptions, shared organisational responsibilities, differing information encodings and formats, and seeking compliance with the LADM ISO 19152 standard, must be considered. Between 2016 and 2018, The Netherlands' Cadastre, Land Registry and Mapping Agency – in short, Kadaster – successfully undertook the renewal of the information system supporting its deeds registration. The previous system dated back to the 1980s. In-house data modelling specialists led the program, the most extensive undertaken in decades. Inspired by action-research principles, the process and resultant lessons are documented using a case study approach. It is shown that beyond Model Driven Architectures, other model-driven methodologies, such as Domain-Driven Design, are entirely useful in the land administration domain. A domain is usually more extensive than a few objects, and to make it more manageable, DDD divides a domain into subdomains. The DDD term 'problem domain' is used to define a functional area within a context such as an organisation or department. The terms domain in DDD and LADM have common characteristics as considering contexts such as a land registry and a cadastre. Evans (2003) and Vernon (2013) articulate how DDD is a set of design practices, techniques and fundamental principles, terms, and implications to facilitate the development of software projects within complex domains, used to guide software developers and domain experts to share and represent models of knowledge from the domain. In DDD, the ubiquitous language is also essential in intersecting the jargons between domain experts and IT experts. The LADM provides a formal language for describing similarities and differences for describing the many aspects of the land administration domain. The approach demands greater participation from domain experts: they lead modelling of the current state and its evolution: the events. The Annex N of ISO 19152 describes that LADM covers both event-based and state-based modelling via LA_Source and VersionedObject. The application of Event-Based Modelling and Event Sourcing is still relatively novel to the LA domain. Event Sourcing ensures that all current state changes are stored as a sequence of events, enabling querying and state reconstruction. The new information system is considered futureproof, delivering improvements for deed registration times, monitoring, traceability/auditing, history management and interoperability. Further research suggestions include undertaken Domain-Driven Design in other contexts, particularly those implementing LADM. Highlights: Domain-Driven Design applied to land administration system development. Event-Driven approach in a deed system for land administration. Event Sourcing and Command Query Responsibility Segregation novel for implementation land administration.